ANALISIS PERAN DIGITAL CONTENT MARKETING BAGI WIRAUSAHA MILENIAL DI KOTA KUPANG DALAM MASA PANDEMI COVID-19 - Klaasvakumok Jehezkielomi Kamuri (Journal of Management Small and Medium Enterprises (SMEs), 2021)
One of the impacts caused by the Covid-19 pandemic is the limited interaction of the community in various activities, including business activities, causing Indonesia to experience a 0.1% decline in economic growth in 2020, and more than 50% of Small and Medium Enterprises have become victims. However, the limited interaction in business activities is not a major problem for the millennial generation. They have sufficient skills and knowledge in utilizing technology to carry out their business activities. The method used today is marketing through digital content which is known as digital content marketing. Many business people have started to switch to modern marketing based on digital technology because it is considered more effective and can be done in various situations and conditions, including during the Covid-19 pandemic. This study aims to examine the role of digital content marketing towards the efforts made by millennial entrepreneurs in Kupang City during the Covid-19 pandemic. The method used in this research is descriptive qualitative in order to obtain data and facts related to the research problem directly. Through the results and discussion, it was concluded that digital content marketing plays an important role in creating cost-effective promotions, increasing sales, communication media and effective and up to date marketing information. Digital content marketing plays a role in building brand awareness and consumer loyalty, being a means of developing creativity and knowledge of business actors in utilizing technology for business, and creating competitive advantages for millennial entrepreneurs in Kupang City. Keywords: Digital Content Marketing, Entrepreneurship, Millennial Generation